2018
DOI: 10.1186/s13098-018-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction study of the association between glycemic variability and diabetes neuropathy

Abstract: BackgroundIt remains unclear whether glycemic variability is related to diabetes microvascular disease, especially diabetes peripheral neuropathy (DPN). We investigated the association between glycemic variability and DPN with type 1 or 2 diabetes.MethodsForty patients (23 males and 17 females; aged 34–79 years) underwent continuous glucose monitoring (CGM) and a nerve conduction study (NCS). Glycemic variability was estimated by mean amplitude of glycemic excursions (MAGE) in CGM. DPN was quantitatively evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The results of the current study indicate that percentage time above target range is strongly associated with worsening peripheral nerve function and our findings also suggest that glucose variability may have an additional role. Nevertheless, the potentially damaging effect of glucose variability is consistent with previous studies, which have observed a relationship between increasing glucose variability, measured over 5 or 6 days, and nerve dysfunction as well as clinical signs of neuropathy in type 1 diabetes [27,28]. Large fluctuations in glucose in type 1 diabetes are associated with oxidative stress and endothelial dysfunction, which may explain how glucose variability causes nerve injury and impairs nerve function [29,30].…”
Section: Discussionsupporting
confidence: 86%
“…The results of the current study indicate that percentage time above target range is strongly associated with worsening peripheral nerve function and our findings also suggest that glucose variability may have an additional role. Nevertheless, the potentially damaging effect of glucose variability is consistent with previous studies, which have observed a relationship between increasing glucose variability, measured over 5 or 6 days, and nerve dysfunction as well as clinical signs of neuropathy in type 1 diabetes [27,28]. Large fluctuations in glucose in type 1 diabetes are associated with oxidative stress and endothelial dysfunction, which may explain how glucose variability causes nerve injury and impairs nerve function [29,30].…”
Section: Discussionsupporting
confidence: 86%
“…Short-term GV was estimated by MAGE in CGM and was found to be independently associated with a higher risk of DPN with type 1 or 2 diabetes [ 70 ], but the study had a small sample size, which might not be able to evaluate patients with severe diabetes complications. Yang et al found that a decreasing level of TIR was significantly associated with an increasing risk of painful diabetic neuropathy, which might be underscored as a valuable clinical evaluation measure [ 71 ].…”
Section: The Role Of Gv In Diabetic Macrovascular and Microvascular Cmentioning
confidence: 99%
“…Mean FBG & PMBG values observed in current study were suggestive of poor glycaemic control & was negatively correlated with conduction velocity. These raised blood glucose level in diabetics can decrease nitric oxide in nerves causing endoneural hypoxia resulting in slowed conduction [14][15][16]. However mild reversible reduction in conduction velocity can be seen without structural changes in myelin due to metabolic causes like hyperglycaemias [5].…”
Section: Discussionmentioning
confidence: 99%